The evolving Semashko model of primary health care: the case of the Russian Federation - Sheiman I; Shishkin S; Shevsky V (Dove Medical Press, 2018)
Igor Sheiman, Sergey Shishkin, Vladimir Shevsky Center for Health Policy, National Research University Higher School of Economics, Moscow, Russia Abstract: This paper addresses the major developments in primary care in the Russian Federation under the evolving Semashko model. The overview of the original model and its current version indicates some positive characteristics, including the financial accessibility of care, focus on prevention, patient lists, and gatekeeping by primary-care providers. However, in practice these characteristics do not work according to expectations. The current primary-care system is inefficient and has low quality of care by international standards. The major reasons for the gap between the positive characteristics of the model and the actual developments are discussed, including the excessive specialization of primary care, weak health-workforce policy, the delay in the shift to a general practitioner model, and the dominance of the multispecialty polyclinic, which does not prove advantageous over alternative models. Government attempts to strengthen primary care cover a wide range of activities, but they are not enough to improve the system and cannot do this without more a systematic and consistent approach. The major lesson learnt is that the lack of generalists and coordination cannot be compensated for by the growing number of specialists in the staff of primary-care facilities. Big multispecialty settings (polyclinics in the Russian context) have the potential for more integrated service delivery, but to make it happen, action is needed. Simple decisions, like merging polyclinics, do not help much. Keywords: health policy, primary health care, general practitioner, Semashko model